2017
DOI: 10.5539/gjhs.v9n10p1
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and Perpetration of Intimate Partner Violence among Female and Male Youth and Adults in South Africa

Abstract: Objective: Intimate partner violence (IPV) is a huge public health problem. The aim of the study was to estimate the prevalence and influence of sociodemographic and health characteristics on IPV victimization and perpetration among women and men 15 years and older in South Africa. Materials and Methods:Data based on the South African national population-based survey in 2012 for 15916 (8532 women and 7384 men) aged 15 years and older who were in an intimate partner relationship were analysed. Bivariate and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…These two groups of women are more likely to be the victims of intimate partner violence (27). This study found intimate partner violence as a significant contributing factor to antenatal depression which is similar to the study conducted by Peltzer et al in Thailand and Insan et al in Bangladesh (12, 28).…”
Section: Discussionsupporting
confidence: 90%
“…These two groups of women are more likely to be the victims of intimate partner violence (27). This study found intimate partner violence as a significant contributing factor to antenatal depression which is similar to the study conducted by Peltzer et al in Thailand and Insan et al in Bangladesh (12, 28).…”
Section: Discussionsupporting
confidence: 90%
“…"In the past 12 months, a partner has forced me to have sex against my wishes by using violence or threatening violence." (Response options were "yes" and "no") [7,9]. A positive response to any of the five questions was classified as intimate partner violence, and a positive response to the second question as sexual violence victimization.…”
Section: Methodsmentioning
confidence: 99%
“…There are multiple factors that contribute to VAW. A growing body of evidence shows that risk factors for VAW are multiple, including socio-demographic factors such as low education, child abuse experiences, alcohol abuse, attitudes accepting VAW and gender inequality (Djakanovic, Jansen & Otasevic, 2010:728;Peltzer, Phaswana-Mafuya & Pengpid, 2017;World Health Organization (WHO), 2016). Therefore it is imperative to understand and explore the risk factors that contribute to the widespread occurrence of VAW, since they have an impact on the progress of the legislative frameworks and programmes that aim to promote the quality of life of women.…”
Section: The Triple Challenge As Risk Factors In Violence Against Womenmentioning
confidence: 99%
“…These multifaceted factors make the problem complex and difficult to combat. Several studies confirm that the risk factors for VAW include poverty, unemployment, income inequality, patriarchal notions of masculinity that valorise toughness, risktaking and defence of honour, exposure to child abuse in childhood, weak parenting, access to firearms, alcohol abuse and weakness in the mechanisms of law enforcement (Gass et al, 2011;Heise & Kotsadam, 2015;Peltzer et al, 2017:2; WHO, 2016:1).…”
Section: The Triple Challenge As Risk Factors In Violence Against Womenmentioning
confidence: 99%